2021
DOI: 10.1113/jp281288
|View full text |Cite
|
Sign up to set email alerts
|

Late gestation fetal hyperglucagonaemia impairs placental function and results in diminished fetal protein accretion and decreased fetal growth

Abstract: Fetal glucagon concentrations are elevated in the setting of placental insufficiency, hypoxia and elevated stress hormones. r Chronically elevated glucagon concentrations in the adult result in profound decreases in amino acid concentrations and lean body mass. r Experimental elevation of fetal glucagon concentrations in a late-gestation pregnant sheep results in lower fetal amino acid concentrations, lower protein accretion and lower fetal weight, in addition to decreased placental function.r This study demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 104 publications
(176 reference statements)
0
8
0
Order By: Relevance
“…While considerable effort has been expended on examining maternal glucose, insulin and IGF1 in normal and compromised pregnancies, the role of maternal glucagon for the most part has been overlooked, although Qiao et al [ 52 ] recently reported that pregnancy in mice induces an expansion of maternal α-cell mass, and an increase in maternal glucagon concentrations during early pregnancy. Furthermore, the demonstration [ 53 ] that fetal hyperglucagonemia during late-gestation results in significant reductions in uterine artery blood flow and placental CSH production and secretion into maternal circulation, without impacting umbilical blood flow or CSH concentrations, highlights not only the importance of glucagon during pregnancy, but also that the three compartments (maternal, placental and fetal) are intimately integrated and need to be investigated together [ 54 ]. This research, therefore, also exemplifies the utility of integrating in vivo RNAi in an animal model that can allow steady-state assessment of altered maternal-placental-fetal physiology [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…While considerable effort has been expended on examining maternal glucose, insulin and IGF1 in normal and compromised pregnancies, the role of maternal glucagon for the most part has been overlooked, although Qiao et al [ 52 ] recently reported that pregnancy in mice induces an expansion of maternal α-cell mass, and an increase in maternal glucagon concentrations during early pregnancy. Furthermore, the demonstration [ 53 ] that fetal hyperglucagonemia during late-gestation results in significant reductions in uterine artery blood flow and placental CSH production and secretion into maternal circulation, without impacting umbilical blood flow or CSH concentrations, highlights not only the importance of glucagon during pregnancy, but also that the three compartments (maternal, placental and fetal) are intimately integrated and need to be investigated together [ 54 ]. This research, therefore, also exemplifies the utility of integrating in vivo RNAi in an animal model that can allow steady-state assessment of altered maternal-placental-fetal physiology [ 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…As described extensively in Table 1 , uterine and umbilical blood flows were calculated by the transplacental diffusion technique described previously [ 13 , 49 , 50 ]. Uterine, umbilical, and uteroplacental utilization of oxygen, glucose, lactate and amino acids were calculated by the transplacental diffusion technique [ 51 ] and reported as an average of draws one through four.…”
Section: Methodsmentioning
confidence: 99%
“…Plasma amino acids were measured by HPLC [ 13 ]. Maternal (uterine) and fetal (umbilical) concentrations of insulin, IGF1, and cortisol were assessed by enzyme-linked immunosorbent assay (ALPCO Immunoassays 80-INSOV-E01, 22-IGFHU-E01, and 11-CORHU-E01-SLV, respectively), as described previously [ 50 , 52 , 53 ]. Estradiol was analyzed by radioimmunoassay, as described by Gonzalez-Padilla et al [ 54 ].…”
Section: Methodsmentioning
confidence: 99%
“…Fetal–placental endothelial dysfunction is characterized by changes in the l -arginine-adenosine signaling pathway and inflammation ( 165 , 166 ). The mechanisms involved in these changes are hypothesized to be hyperglycemia, hyperinsulinemia, and oxidative stress ( 167 , 168 ). These conditions increase the release of exosomes.…”
Section: Exosomes As a Potential Therapeutic Target For Diabetes Mellitus And Diabetic Complicationsmentioning
confidence: 99%